2011
DOI: 10.1007/s12272-011-1111-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of emulsified solid dispersions containing docetaxel

Abstract: An emulsified solid dispersion of docetaxel was prepared and characterized in vitro. In contrast to conventional solid dispersions, emulsifying pharmaceutical excipients and hydroxypropyl methylcellulose (HPMC) as a supersaturation promoter were introduced into the PEG6000-based solid dispersion to further improve its solubilizing capability. The solubility, dissolution in vitro and stability of the prepared emulsified solid dispersions were studied taking into consideration of the effects of different emulsif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The temperatures ranged from 2°C to 60°C and the relative humidity varied between 0% and 100%. The duration also varied significantly, with stability studies lasting from 24 h to two years (73,74,81,82,84,86,88,92,93,104,105,109,110,113,115,116,118,120,123,124,126,127,129,130,132,134,135,139,143,146,149,153,158,166,169,172,175,176). While most of the studies did not mention the container used for the physical stability test, a few specified, for example, whether a closed or open container was used (88,92,113,123,132,146).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperatures ranged from 2°C to 60°C and the relative humidity varied between 0% and 100%. The duration also varied significantly, with stability studies lasting from 24 h to two years (73,74,81,82,84,86,88,92,93,104,105,109,110,113,115,116,118,120,123,124,126,127,129,130,132,134,135,139,143,146,149,153,158,166,169,172,175,176). While most of the studies did not mention the container used for the physical stability test, a few specified, for example, whether a closed or open container was used (88,92,113,123,132,146).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…Ninety-two of the 101 studies reported solubility and dissolution studies (7174,7779,8192,95,97107,109111,113119,121,123,124,126133,135139,141154,156,157,160,161,166,168176). The USP in vitro dissolution type II apparatus was the most commonly used instrument (67%), followed by the USP type I apparatus (6%), while the remaining 27% used various other apparatuses, including modified versions of the USP type I only (148) or paired with confocal Raman microscopy (98), USP types I and II apparatus (72), USP type IV (152), closed loop of USP types II and IV (152), a perspex flow cell (73,142), a rotary mixer (131), a Chinese pharmacopoeia type III apparatus (118), an in-house miniaturized USP type II apparatus (175), Sirius T3 apparatus (146), μFLUX dissolution-permeation apparatus (141), Raman UV-Vis flow cell system (99), a centrifuge (88), high throughput screening using a 96-well plate (82,115,157), Wood’s apparatus (99,137), an orbital shaking incubator (156), and another shake-flask method (171) (Fig. 6).…”
Section: Current Status Of Research On Amorphous Formulationsmentioning
confidence: 99%
“…The results showed a 134-fold increase in dissolution rate for SD containing 30/70 w / w fenofibrate/ poloxamer 407. Surfactants are also used in preparation of SD of poorly soluble anticancer drugs such as docetaxel [76], flutamide [77], and lapatinib [78].…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…In vitro release of the drug from the SD was 4.35-fold greater than that of the pure drug after 2.5 h. In addition, the oral BA of the drug from the SD was higher than that of the conventional drug as determined by AUC (4.8-fold) and C max (13.1-fold). The solvent evaporation method has often been used to improve solubility of poorly water-soluble anticancer drugs such as paclitaxel [133], docetaxel [76], and others (Table 3). For example, the solubility and dissolution of emulsified SD of docetaxel at 2 h were 34.2- and 12.7-fold greater, respectively, compared to those of the conventional drug [76].…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…However, it also requires the therapeutic dose of API to be low. For instance, Chen et al prepared emulsified SDs containing docetaxel by three approaches, i.e., melting method, solvent-melting method and solvent method [ 71 ]. It was shown that the dissolution of docetaxel from SDs prepared by the solvent-melting method was higher than that prepared by the melting method.…”
Section: Solid Dispersion Techniquementioning
confidence: 99%